Online or not? A comparison of students' experiences of an online and an on-campus class - Tennyson Mgutshini (AOSIS, 2013)
Educational discourse has long portrayed online, or e-based, learning and all non-campus-based learning options as second best to traditional face-to-face options. Critically much of the research and debate in this area of study has focused on evidence relating to student performance, attrition and retention with little consideration of the total learning experience, which values both the traditional learning outcome measures side-by-side with student-centered factors, such as students' satisfaction with their learning experience. The objective of this study was to present a synchronous head-to-head comparison between online and campus-based students' experiences of an undergraduate course. This paper reports on a qualitative comparative cross-sectional study, which used multiple data collection approaches to assess student learning and student satisfaction of 61 students who completed a semester of an undergraduate course. Of the 61 students, 34 were enrolled purely as online students, whilst the remaining 27 students studied the same material entirely through the traditional face-to-face medium. Methods included a standardised student satisfaction survey and an 'achievement of learning outcomes' measurement tool. Students on the online cohort performed better in areas where 'self-direction' in learning was indicated, for example self-directed problem-based tasks within the course. Online students gave less positive self-assessments of their perceived content mastery than their campus-based counterparts, despite performing just as well in both summative and formative assignments. A multi-factorial comparison shows online students to have comparable educational success and that, in terms of student satisfaction, online learners reported more satisfaction with their learning experience than their campus-based counterparts.